Prioritizing Parkinson’s disease genes using population-scale transcriptomic data - Yang I. Li (Nature Portfolio, 2019)
GWAS have identified over 41 susceptibility loci for Parkinson’s disease (PD). Here, the authors integrate PD GWAS summary statistics with transcriptome data from monocytes and DLFPC tissue in a TWAS approach and find 66 significant associations with PD risk highlighting lysosomal and innate immune functions.